Entrepreneurship Education: Is It Important for Middle School Students? - Rina, Lelahester; Murtini, Wiedy; Indriayu, Mintasih (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
The aim of this research is to know the important role of the entrepreneurship education program in the school institution. Entrepreneurial trait is needed in any fields of work regarding to the technology development today. Thus, entrepreneurial education needs to be applied in any levels of education as it has an important role for preparing skillful and creative graduates. This study focused on the interesting phenomena of the school effort in integrating entrepreneurship to other subjects and also the application of the entrepreneurship in Satya Wacana Christian Junior and Senior High Schools Salatiga. This study was done by qualitative approach through snowball sampling technique. Data were obtained through observations, interviews, and documentation of the participants who understand the information and central phenomena. Research data analyzed by the analysis of the domain from Spradley. The result of the study showed that entrepreneurship education had an important role to improve the entrepreneurial knowlegde and skills. The integrated education, either in the learning process or in the school entrepreneurship education program, increased the entrepreneurship understanding, character, and behavior. This study is significant because it gives a contribution the schools and students to understand the importance of entrepreneurship education.